KETERLIBATAN AUSTRALIA DI DALAM QUAD (QUADRILATERAL SECURITY DIALOGUE) DAN IMPILIKASINYA TERHADAP KEBIJAKAN PERTAHANAN AUSTRALIA TAHUN 2017-2021 - Audrian, Hafiztra; Saeri, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The rise of China has been a major determinant in the rise of the Quad initiative and the group's new initiatives in aggressive foreign policy. Australia's approach to the Quad has changed significantly since participating in the Malabar naval exercises in 2007. The formulation of the problem in this study is how Australia's involvement in the Quad (quadrilateral security dialogue) and its implications for Australia's defense and security policy. The purpose of this study is to analyze what interests Australia has in being involved in the Quad and the implications of Australia's membership in the Quad for foreign policy. The theory used is the Alliance Theory. This study uses a qualitative method, with data collection techniques through literature studies sourced from several books, journals, articles, websites. This study uses a document-based research study method, namely a research method carried out by analyzing documents that have a high level of relevance to the topic being studied. Australia in the Quad can collaborate to fund infrastructure projects in the Indo-Pacific, create business opportunities for Australian companies, so that it has an agenda to improve connectivity in the Indo-Pacific region, which includes transportation, communications, and digital trade, so as to grow the economy and strengthen defense and security for Australia itself. Keywords: Australia; Policy; Quad.